Technologies for strengthening the image of a political leader in the modern information space: political psychology - Gabdulina Б.А.; Uali Б. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
As a mechanism for influencing the political consciousness of society, attention should be paid to the best achievements of political psychology. In this regard, the psychology of the masses is the object of influence of political power, in this regard, we have reviewed the works of famous world scientists who study the psychology of the masses and the individual, and in the future to use their conclusions in their future research work. Therefore, in order to achieve the goal of the research work, the psychological basis of influence on the socio-political consciousness was considered in order to optimize the use of political technologies and obtain appropriate results.